Magnetic-free non-reciprocity based on staggered commutation - Negar Reiskarimian (Nature Portfolio, 2016)
Components such as isolators, circulators and gyrators are non-reciprocal in that they allow electromagnetic waves to flow in one direction but not the other. Here, the authors demonstrate a radio-frequency circulator that is compatible with and integrated in a complementary metal-oxide semiconductor integrated circuit.